Adaptation and validation of the ITC - Sense of Presence Inventory for the Portuguese language. Issue 125 (May 2019) - Vasconcelos-Raposo, José; Melo, Miguel; Teixeira, Carla; Cabral, Luciana; Bessa, Maximino
Highlights: An adaptation of the popular ITC - Sense of Presence Inventory questionnaire to the Portuguese Language. A theoretical model of the ITC-SOPI that allows to measure presence in virtual reality research projects with samples of Portuguese language. A validation of the adapted to Portuguese version of the ITC - Sense of Presence Inventory that is equivalent to the original version as well as the validity of the contents and concepts, to ascertain the psychometric properties of the instrument. Abstract: This investigation concerns the translation and validation of the ITC - Sense of Presence Inventory (ITC-SOPI) for the Portuguese-speaking population (in Europe), estimating the validity of the content and concepts and the maintenance of an equivalent semantics. It also sought to verify its psychometric properties, namely its factorial validity and internal consistency. The sample consisted of 459 individuals, 274 males and 185 females. The fidelity of the subscales varied between 0.67 and 0.89. Confirmatory factor analysis revealed a theoretical model of 35 items, divided by four factors. After fixing some of the residual errors between items, the following adjustment indexes were calculated: χ 2 / df = 2.301; goodness fit index = 0.860; comparative fitness index = 0.889; root mean square error of approximation = 0.053; Akaike's information criterion = 1420. Based on the observed results and the robustness of the sample size used, the obtained theoretical model shows that the ITC-SOPI is recommended to measure presence in virtual reality research projects with samples of Portuguese language speakers.